AB0095 Forelimb Development in the Mouse: an Original Model of Organo-Dependent Lymphangiogenesis. (10th June 2014) - Nguyen, C.; Skoczylas, R.; Pichol-Thiévend, C.; Frampton, E.; Rannou, F.; François, M.
Abstract : Background: Quantitative and qualitative changes affecting the lymphatic network are associated with limb and joint diseases including rheumatoid arthritis and osteoarthritis at the adult age. However how lymphatics develop during embryogenesis in the limbs remain largely unexplored. Objectives: To describe for the first time lymphangiogenesis in mouse forelimbs and joints during early embryogenesis. Methods: Prox1 is a key transcription factor involved in lymphatic specification and remodelling. Taking advantage of the Prox1-GFP reporter transgenic mouse line, we described lymphangiogenesis in the forelimbs and in the joints during early embryogenesis from 9.5 (E9.5) to 14.5 (E14.5) days post-coitum using confocal imaging on fixed samples stained with specific markers for lymphatic and vascular endothelia, as well as for surrounding specifying tissues including cartilage, muscles and peripheral nerves. Timelapse imaging was also performed on specimens collected at E11.5 and E12.5 to address lymphangiogenesis ex vivo . Results: From E9.5 to E10.5, Prox1 positive cells emerge directly from the cardinal vein and are located at the limb bud, following an antero-posterior gradient. Elongated shape suggests migrating cells. Other markers for lymphatics including neuropillin-2 and endothelium including endomucin are expressed in a dense unpatterned vascular network involving the future forelimb suggesting an undifferentiated primary capillary plexus. From E11.5 to E12.5, this unpatterned network undergoes an extensive remodelling with the formation of an avascular zone as the skeleton mesenchyme is condensing. More strikingly, Prox1 positive cells emerge directly from this capillary plexus, suggesting an original mechanism of local lymphangiogenesis. In addition to this process, ex vivo imaging at E11.5 and E12.5 reveals that sprouting, branching, cell division and networking from the forelimb marginal vein also occur, still following an antero-posterior gradient. Later on, vascular network patterning is coordinated to other tissues specification including peripheral nerves, joints and muscles. Conclusions: Altogether, our data suggest that the development of lymphatics in the forelimb represents an original model of organo-dependent lymphangiogenesis associating migration from the cardinal vein and local lymphangiogenesis from local precursors. Acknowledgements: Dr Christelle Nguyen received fundings from the French Society of Rheumatology (SFR), the French Society of Rehabilitation Medicine (SOFMER) and the Bettencourt-Schueller Foundation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3954